The Effect of Financing Portfolio Diversification Strategy on The Risk of Non Performing Financing in The Indonesian Islamic Banks - Ihdina Sabilal Haq (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
Purpose – The purpose of this study is to examine the effect of a credit portfolio diversification strategy on the risk of bad loans in Islamic banking in Indonesia for the 2018-2022 period. Design/methodology/approach – Exogenous variables in this study include credit portfolio diversification based on contract and type of usage. Meanwhile, the endogenous variable is the risk of bad credit in Islamic banking. The loan portfolio diversification variable based on the contract and type of use is calculated using the Herfindahl-Hirschman Index (HHI). The bad credit risk variable uses the Non Performing Financing (NPF) proxy. The population in this study are Islamic Commercial Banks and Sharia Business Units in 2018-2022 using a saturated sample technique. In addition, Ordinary Least Square (OLS) Regression Analysis is used in the data analysis method. Findings – The results of this study indicate that the diversification of the credit portfolio based on the contract and the type of usage both partially and simultaneously has a significant effect on the risk of bad credit in Islamic Banking. Research limitations/implications – This study is limited to Islamic commercial banks and Islamic business units in Indonesia. There are three types of financing, namely financing based on contract-, type of use and business sector and not the business sector of credit beneficiary, but in this study only uses diversification of financing based on contracts and usage due to limited data and research time. Practical implications – The role of credit diversification based on contract and type of usage in reducing the risk of bad credit that may be useful for sharia banking, both sharia commercial banks and sharia business units in Indonesia, is related to the need for a credit portfolio diversification strategy policy to reduce the risk of bad credit in companies as well as for further researchers as an additional reference. for research that uses the topic of factors that influence the level of credit risk in Islamic banking. Originality/value – This study provides new insights about the role of credit diversification based on contracts and the type of use that can significantly affect the risk of bad credit in Islamic banking in Indonesia.